Community epidemic management strategies and COVID-19 in South Sudan - Nicki Kindersley; Joseph Diing Majok (Health and Social Sciences Research Institute - South Sudan (HSSRI-SS), 2021)
South Sudanese people have extensive knowledge and experience of responding to infectious diseases and epidemic outbreaks. This research investigated existing community infectious disease management strategies outside of the clinical healthcare sector, to better understand how communities respond to infectious disease outbreaks. The research demonstrates extensive local methods for infection control and epidemic management which, while they may not reach current clinical standards, provide a strong foundation for collaborative approaches to stopping the spread of COVID-19 and other dangerous diseases. The research suggests that working with local strategies and frontline non-clinical healthcare providers is key to building a trusted and sustained response to COVID-19 and other epidemics.